Changes in Rous Sarcoma Virus RNA Secondary Structure near the Primer Binding Site upon tRNA(Trp) Primer Annealing - Morris, Shannon (American Society for Microbiology (ASM), 1999)
Predicted secondary-structure elements encompassing the primer binding site in the 5′ untranslated region of Rous sarcoma virus (RSV) RNA play an integral role in multiple viral replications steps including reverse transcription, DNA integration, and RNA packaging (A. Aiyar, D. Cobrinik, Z. Ge, H. J. Kung, and J. Leis, J. Virol. 66:2464–2472, 1992; D. Cobrinik, A. Aiyar, Z. Ge, M. Katzman, H. Huang, and J. Leis, J. Virol. 65:3864–3872, 1991; J. T. Miller, Z. Ge, S. Morris, K. Das, and J. Leis, J. Virol. 71:7648–7656, 1997). These elements include the U5-Leader stem, U5-IR stem-loop, and U5-TΨC interaction region. Limited digestion of the 5′ untranslated region of wild-type and mutant RSV RNAs with structure- and/or sequence-specific RNases detects the presence of the U5-Leader stem and the U5-IR stem-loop. When a tRNA(Trp) primer is annealed to wild-type RNAs in vitro, limited nuclease mapping indicates that the U5-IR stem becomes partially unwound. This is not observed when mutant RNAs with altered U5-IR stem-loop structures are substituted for wild-type RNAs. The U5-Leader stem also becomes destabilized when the tRNA primer is annealed to either wild-type or mutant RNA fragments. Nuclease mapping studies of tRNA(Trp), as well as the viral RNA, indicate that the U5-TΨC helix does form in vitro upon primer annealing. Collectively, these data suggest that the various structural elements near the RSV primer binding site undergo significant changes during the process of primer annealing.